Fermentasi Kopi Robusta Dengan Lactococcus lactis subsp.Untuk Meningkatkan Kualitas Rasa Kopi - Enny Nurmalasari; Kusmiyati; Agung Kurnia Yahya; Agnes Heratri; Sinju Kunikazari (Politeknik ATI Padang, 2024)
Fermentation in coffee provides new modulation to the taste and sensory profile of coffee, thereby enhancing its flavor quality. Lactic Acid Bacteria (LAB) strains are used for fermentation in the wet process and have been proven to improve the overall flavor of the coffee. Therefore, in this study, coffee fermentation will be carried out using Lactococcus lactis subsp. to improve coffee flavor quality. The study begins with preparing the starter medium, starter culture, and fermentation. Subsequently, proximate analysis and a cupping test are conducted to assess the flavor profile of the coffee. The results of this study show that coffee fermentation can increase the number of LAB with longer fermentation times. Furthermore, proximate results indicate that fermented Robusta coffee contains 7.86% less fat compared to non-fermented Robusta coffee, which has 15.02% fat. The cupping test results for fermented Robusta coffee reveal a total score of 81, with the clean cup and uniformity aspects scoring 10. This total is higher than that of non-fermented Robusta coffee, thus proving that fermentation using Lactococcus lactis subsp. can improve coffee flavor quality.